Suplementações energéticas alternativas para cabras Saanen lactantes em pastejo - Olivo, Paula Martins (2016)
The objective of this study was to characterize and evaluate the dry matter intake and supplementation of nutrients for Saanen goats, and its effects on production, composition, quality of milk and blood parameters. Five Saanen goats after 60 days in milk production (55.56 i 4.94 kg of body weight) were distributed in 5x5 Latin square design receiving diets composed by grass Star (Cynodon nlemfuensis) and energy supplementation containing soybean meal, mineral-supplement vitamin, salt and different energy sources: ground corn, corn + protected fat, soybean hulls, corn cobs and disintegrated with straw and dry cassava byproduct. The contents of dry matter, ash, crude protein, ether extract, neutral detergent fiber, acid detergent fiber, gross energy and digestibility in vitro of dry matter were determined. We estimated organic matter, total carbohydrates and non-fibrous carbohydrates. The dry matter intake, pasture nutrients and pasture digestibility were estimated by using external indicator (Cr2O3) and internal indicator (FDAi) and supplement intake and digestibility was estimated by the difference between the supplied food and leftovers in the days of collection period. The control of milk production was done by weighing this every milking. Milk samples were collected and sent to the Laboratory of the Program Analysis of Parana Dairy Herd, belonging to the Cattle Breeders Paranaense Association of Holstein, to determine the content of protein, fat, lactose, total solids and somatic cell count (CCS). Also milk samples were collected to measure the fatty acid profile. Goats blood samples were collected to analyze the concentrations of glucose, triglycerides, cholesterol and urea. There were differences (P<0.05) for ether extract intake and non-fibrous carbohydrates between supplementation, but there were no differences (P>0.05) for dry matter intake, organic matter and crude protein. Treatments containing ground corn and bark of soybean showed better results for digestibility. The milk production and milk production corrected for 35 g fat/ kg of milk and its composition have not changed with the different energy sources. ln profile analysis of fatty acids l4: l myristoleic, 15: 0 pentadecanoic, and 18: 0 stearic showed differences (P<0.05) between the supplementation. In blood parameters, glucose, triglycerides and cholesterol did not differ (P>0.05) between the supplementation, but urea was different (P<0.05), with the highest Value in soybean hulls. The lowest value was obtained for urea nitrogen in milk supplementation with ground corn and cob (P<0.05). The supplementations with alternative energy sources in the diet of lactating Saanen goats do not alter the dry matter intake, milk production, composition and quality. About digestibility, the best results can be assigned to treatments containing ground corn and soybean hulls.